Ocean Wave Energy Converter Mid-Fidelity Numerical Simulation Tools: A Review (Proceedings of the European Wave and Tidal Energy Conference, 2025)
Ocean wave energy holds immense potential as a renewable energy source, offering a vast, untapped resource. Despite this, wave energy converters (WECs) are still in their technological infancy, and their levelized cost of energy (LCoE) is not yet competitive compared to other generation sources. Most devices currently reside at technology readiness levels (TRL) 3 through 5, relying heavily on mid-fidelity numerical modelling to proceed toward commercial viability. WEC developers often develop these tools in-house and for bespoke needs, meaning few are publicly available and flexible enough to meet the diverse needs of end-users.The past decade has marked the emergence of dedicated mid-fidelity WEC numerical modelling and simulation tools. In driving WEC designs towards commercial viability, a comparative evaluation of these tools is critical; it builds confidence in their reliability by helping understand the nuances between differing fundamental assumptions and modelling approaches, leading designers to make informed choices. Although several reviews were published shortly following the release of these tools in the mid-to-late 2010s, it has been some time since an updated thorough analysis has been performed. Over this period, some tools have undergone significant developments, whereas others have since been discontinued, creating a gap in the literature. Furthermore, existing analyses have focused on reviewing specific components through code-to-code comparisons, rather than a holistic discussion of the underlying fundamental theory and available features, leaving users without a clear understanding of subtle distinctions between tools.This study seeks to provide a qualitative analysis of publicly available ocean wave energy simulation tools, helping users navigate the market and select the technology that best suits their needs. Key features being examined include formulations of the hydrodynamics, wave, mooring, PTO and control problems, and the multibody dynamic solver. Within these domains, minute variations in assumptions and modelling approaches define the distinctions between tools. Namely, it is the distinction of formulating the hydrodynamic problem using Morison’s and/or Cummins equation. Additionally, some tools are designed for general ocean engineering applications and thus have limited capacity to model and simulate features specific to wave energy such as a PTO and associated control.This review offers valuable insights into the distinctions between general mid-fidelity wave energy simulation tools and aims to assist designers in selecting the tool best suited to meet their unique requirements.